2018
DOI: 10.29252/nrip.hdq.3.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Associating Factors With Public Preparedness Behavior Against Earthquake: A Review of Iranian Research Literature

Abstract: Local preparedness against earthquakes has been recently highlighted in research and policies on disaster management and risk reduction promotion in Iran. To advance the understanding of public preparedness and how it can be applied in diverse localities, further information is required about the predictors of people's adoption of mitigation activities and earthquake preparedness. A synthesis of the available published research results on earthquake preparedness and the influencing factors in Iran are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In Najafi et al's study (2018), which interviewed 132 heads of households living in Tehran, lack of knowledge and insufficient time were identified as the most important barriers to earthquake preparedness ( 18 ). A review study showed that Iranians with a higher knowledge level had a better performance in preparing for an earthquake ( 23 ). In Appleby et al's study in Romania and Malta (2021), most participants were unaware of disaster preparedness guidelines, and those with more knowledge reported greater preparedness ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Najafi et al's study (2018), which interviewed 132 heads of households living in Tehran, lack of knowledge and insufficient time were identified as the most important barriers to earthquake preparedness ( 18 ). A review study showed that Iranians with a higher knowledge level had a better performance in preparing for an earthquake ( 23 ). In Appleby et al's study in Romania and Malta (2021), most participants were unaware of disaster preparedness guidelines, and those with more knowledge reported greater preparedness ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the higher a person's self-efficacy is, the more intention there is for preventive measures and preparedness against disasters. In a review conducted by Ranjbar et al, Iranians who had more self-efficacy reported more earthquake preparedness behaviors ( 23 ). In Ning et al's study in China (2021), people with higher self-efficacy had more emergency preparedness behavior ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts to public disaster education and a generally good level of risk perception among Tehran citizens (75%>Median score) ( 15 ), the majority are not prepared for the probable earthquake yet ( 10 , 15 – 17 ). The governmental and local attempts to enhance earthquake preparation in general, were not capable of facilitating sufficient public preparedness ( 18 ). This highlights the need for a better understanding of the factors influencing on high-risk communities preparedness ( 10 , 19 ).…”
Section: Introductionmentioning
confidence: 99%